The Role of Self-Efficacy in Improving the Adversity Quotient of Employees - Rahmat Ramadan; Dwi Huriyati (Faculty of Psychology, Universitas Semarang, 2023)
Self-efficacy is one of the factors that can increase individual adversity quotient; this study aims to see the relationship between self-efficacy and adversity quotient in employees of PT XYZ Palembang. This research method uses a correlational quantitative approach; the subjects in this study were 105 employees of PT XYZ Palembang using simple random sampling. The research instrument used is the psychological scale of self-efficacy and adversity quotient. Furthermore, the data were analyzed using a simple regression test. The results of this study obtained a relationship between self-efficacy and adversity quotient in employees of PT XYZ Palembang with the results of hypothesis testing obtained, namely the results obtained based on the correlation value between the self-efficacy variable and adversity quotient, namely with a value of r = 0.397 with a value of R square = 0.157 and p = 0.000 where the value of p < 0.01. This shows that there is a relationship between self-efficacy and adversity quotient in employees of PT XYZ Palembang.Keywords: self-efficacy, adversity quotient, holding company